Research on design strategies and sensing applications of energy storage system based on renewable methanol fuel - Zhang, Rongji; Cao, Jiamu; Wang, Weiqi; Tan, Endong; Zhu, Rui; Chen, Weiping; Zhang, Yufeng (Results in engineering, 2023)
The rapid depletion of traditional non-renewable fossil fuels has increased energy sustainability threats. Methanol is recognized as one of the viable alternatives to conventional fossil fuels mainly due to its high energy density and abundant raw materials. Direct methanol fuel cells (DMFCs) can convert the chemical energy of methanol into electricity in real time, which is one of the most effective ways to utilize methanol energy. However, DMFCs have undesirable performance, such as low fuel utilization, low cell voltage, and unstable output voltage, hindering the development of methanol energy technology. Herein, we design an energy storage system with high methanol energy efficiency based on passive micro DMFCs. This system with low power consumption (only uW scale) can extract the high chemical energy in methanol, efficiently convert it into electric energy, and store it to output a stable voltage for load. Moreover, application research on this system has been carried out. A self-powered methanol concentration sensor is designed and implemented on a printed circuit board. It can detect methanol solution with a concentration of 3 M–12 M, only requiring it to be tested as fuel without an additional power supply. The sensor has about 1.1 mW total power consumption and 0.34 s response time. This study on the energy conversion and storage of sustainable methanol fuel aims to provide a reference to explore the application of renewable energy. •A new energy storage system for methanol fuel cells is designed successfully.•High chemical energy in methanol is extracted efficiently by energy storage system.•A self-powered methanol concentration sensor is designed based on the system.